Fungi as an aetiological factor of upper respiratory diseases - Kurnatowsk, Piotr; Raczyńska-Witońska, Grazyna (Wiadomości parazytologiczne, 2004)
Mycologic investigations were carried out in subjects suffering from upper respiratory tract ailments. The material for assessment was collected from various ontocenoses. Species of fungal strains were determined by means of the morphological and biochemical analyses. Special attention was paid to the frequency of fungi occurring in multiple foci of the same system. In patients presented with ailments of the upper respiratory tract the presence of fungi, predominantly species of Candida genus was detected in different ontocenoses. In 1/4 of cases the fungi were found in 2 or 3 foci, which can induce systemic transmission, interfere with treatment and result in recurrent infections.